Influencing factors Le Minerale: Purchase Decisions - Reghina Reghina; Selvi Yanti T Universitas; Gita Nur Fitriyani Subagio (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
The purpose of this study is to determine whether environmental awareness, green product advertising, environmental knowledge, and green buy intention can affect each other as well as whether Makassar residents' environmental knowledge is influenced by their intentions to make green purchases. Descriptive research methodologies are used in this study. Data from samples in Makassar were also gathered by researchers via an online survey method. Makassar population sampling is made easier with the use of the probability sampling technique. The study's findings indicated that while environmental knowledge had a positive and significant impact on green purchase intention, green purchase intention had a positive and significant impact on environmental knowledge, and environmental awareness and green product advertising had a positive but not statistically significant effect on green purchase intention. The restricted sample size of 164 respondents resulting from time constraints during the research process is the research's main weakness.